Patient-activated three-dimensional multifrequency magnetic resonance elastography for high-resolution mechanical imaging of the liver and spleen - Guo, Jing; Hirsch, S.; Streitberger, K. J.; Kamphues, Carsten; Asbach, Patrick; Braun, Jurgen; Sack, Ingolf (Röfo-Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2014)
Purpose: To introduce a novel in-vivo three-dimensional multifrequency magnetic resonance elastography (3D-MMRE) method for high-resolution mechanical characterization of the liver and spleen. Materials and Methods: Ten healthy volunteers were examined by abdominal single-shot 3D-MMRE using a novel patient-activated trigger system with respiratory control. 10 contiguous slices with 2.5mm cubic voxel resolution, 3 wave components, 8 time steps, and 2 averages were acquired at 7 mechanical excitation frequencies from 30 to 60Hz. The total imaging time was approximately 15min. For postprocessing, multifrequency dual elasto-visco (MDEV) inversion was used to calculate high-resolution mechanical parameter maps of the abdomen including the liver and spleen. Results: Two parameters maps were generated from each image slice to capture the magnitude and the phase angle of the complex shear modulus. Both parameters depicted the mechanical structures of the abdomen with unprecedented high spatial resolution. Spatially averaged group mean values of the liver and spleen are 1.27±0.17 kPa and 2.01±0.69 kPa, indicating a significantly higher asymptomatic stiffness of the spleen compared to the liver. Conclusion: Patient-activated respiratory-gated 3D-MMRE combined with MDEV inversion provides highly resolved mechanical maps of the liver and spleen that are superior to previous elastograms measured by abdominal MRE. Citation Format: Guo J, Hirsch S, Streitberger KJ etal. Patient-Activated Three-Dimensional Multifrequency Magnetic Resonance Elastography for High-Resolution Mechanical Imaging of the Liver and Spleen. Fortschr Röntgenstr 2014; 186: 260-266.© Georg Thieme Verlag KG Stuttgart.
CRIS-Team Scopus Importer:2022-08-03
Keywords: abdomen; liver; magnetic resonance elastography; MR imaging; spleen